EVALUASI PENERAPAN SISTEM INFORMASI PELAYANAN DESA MELUNG MENGGUNAKAN METODE UTAUT 2 - Luzi Dwi Oktaviana; Desty Sandra Utami (JURNAL REKAYASA INFORMASI, 2021)
The village service information system is an application to assist the village government in an effort to provide excellent service to the community through the availability of data and is integrated with an information system that is created and developed specifically according to the needs and problems surrounding services in the village government. As in the village of Melung Kec. Cilongok, the application of service information systems in the village aims to grow a sense of self-service technology. The importance of the introduction and application of technology can help Melung Village towards the concept of a smart village in accordance with technological developments that are currently developing rapidly. Because of these possible problems, it is necessary to hold an evaluation by applying the UTAUT2 method model to determine the factors that influence the use of the public service system seen from the independent variables Performance Expectancy (X1), Effort Expectancy (X2), Social Influence (X3), Facilitating Condition (X4), Hedonic Motivation (X5), Price Value (X6), Habit (X7) on the dependent variable Behavioral Intetnion (Y) in implementing the village service system, namely SILANDESI.id so that users can understand and feel comfortable using the village service information system that is in Melung Village, Cilongok District.